TUTUR KESUSILAAN SANG WIDURA DALAM GAGURITAN WIDURA NITI WAKYA - I Wayan Jatiyasa (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2020)
This study aims to describe: the narrative structure and moral advice of the Widura in Geguritan Widura Niti. Based on the results of the study it was found that: 1) the narrative structure in Gaguritan Widura Niti Wakya, namely: (1) synopsis, tells about the consideration or advice of the Thistle to King Dhrtarastra; (2) the theme is the teaching of decency; (3) setting includes setting of place and time; (4) the flow used is forward flow; (5) characters include the main characters (Raja Dhrtarastra and the Widura), secondary / complementary figures (Sang Hyang Sanatkumara and Sang Kaurawa); (6) characterization: characterization of the Dhrtarastra (kind, merciful); characterization of the Widura (smart and knowledgeable, strong belief in religious teachings); characterization of Sang Hyang Sanatkumara (knowledgeable about God); and characterization of the Duryodhana (arrogant and selfish); (7) mandate (do not oppose destiny, omnipotence, Ida Sang Hyang Widhi Wasa / God, a leader should prioritize the welfare of the people. 2) Speak the decency in the Gaguritan Nidur Wakya Widura, namely: (1) Tri Rich Parisudha (wacika parisudha, kayika parisudha, and manacika parisudha); (2) Panca Yama Brata (brahmacari, Satya and asteya); (3) Panca Nyama Brata (akrodha, susrusa teacher, sauca, aharalaghawa, and apramadha); and (4) Chess Paramita (maitri and karuna).